BIOM-31. TEMPOROSPATIAL PROTEIN PROFILING OF HUMAN GLIOBLASTOMAS REVEALS MOLECULAR MECHANISMS AND BIOMARKERS UNDERLYING RESPONSES TO IMMUNE CHECKPOINT INHIBITION. (14th November 2022) - Young, Jacob S; Lucas, Calixto-Hope; Seo, Kyounghee; Nguyen, Minh; Chen, William; Solomon, David A; Berger, Mitchel S; Phillips, Joanna J; Aghi, Manish; Raleigh, David
Abstract: Glioblastoma responses to immune checkpoint inhibition (ICI) are rare, and the molecular mechanisms underlying ICI responses are incompletely understood. Thus, serial glioblastoma samples are valuable resources for identifying biomarkers or therapeutic targets to increase the efficacy of ICI in patients with glioblastoma. We obtained paired glioblastoma samples from 7 patients who underwent sequential surgery, ICI, and eventual salvage surgery for recurrence. Patients were distinguished as ICI responders (n=3) or non-responders (n=4) based on (1) MRI evidence of tumor stability/reduction over 6+ months after ICI, or (2) pathologic evidence of predominant treatment effect at the time of salvage surgery after ICI. FFPE sections from each tumor (n=14) were stained using H&E or IHC/IF for macrophages/microglia (CD68) or T cells (CD3) and analyzed using light or fluorescence microscopy. Six regions-of-interest (ROIs) comprising viable tumor were selected neuropathologist from each sample (n=84 ROIs). ROIs were analyzed using quantitative spatial profiling of 72 proteins on the Nanostring Digital Profiler platform. Glioblastomas responding to ICI were enriched in T-cell proteins (CD3, CD4, CD8) and T-cell activation markers (CD25) at the time of salvage compared to initial surgery. Markers of MAPK signaling were suppressed in pre-ICI samples compared to post-ICI samples in responders. p-ERK was suppressed in post-ICI samples compared to pre-ICI samples in non-responders. Myeloid proteins (CD68, CD163, CD11c) were enriched in post-ICI samples compared to pre-ICI samples in non-responders. Principle components analysis revealed p-ERK and immune proteins (CD3, CD4, CD8, CD20, CD11c, CTLA4, CD68, CD45, CD56, and CD127) accounted for 62% of the variance among pre-ICI and post-ICI samples in responders. In conclusion, temporospatial protein profiling of human glioblastomas reveals molecular mechanisms and biomarkers underlying responses to immune checkpoint inhibition. These data establish a foundation for functional studies to reprogram the immunosuppressive glioblastoma microenvironment and sensitize tumors to immune checkpoint inhibition.